O entrelaçamento fato-valor : uma abordagem a partir de Hillary Putnam e Amartya Sen - Ferreira, Carlos Roberto Bueno (2015)
This thesis aims to analyze the dichotomy between fact and value. The separation of the merely factual-objective of which is evaluative-subjective is the result of a historical progression based on a number of theories that oppose each other, going back to the clash between Descartes and Hume (rationalism and empiricism). However, this dichotomy is criticized by Hilary Putnam, who defends the existence of an entanglement of facts and values. In this sense, will seek to demonstrate the danger to defend the ideal of a science free of ethical and social values. The second chapter, in order to demonstrate a more tangible way the entanglement between facts and values, is dedicated to an evaluation conducted on the unsustainability of the dichotomy fact - value in the economy. It is proposed to evaluate the work of Amartya Sen, Indian philosopher and economist who has devoted his career to the affirmation of the economy also as a human science that deals with complex ethical factors which can not be reduced simply to numbers and statistics.Sen defends the possibility of a welfare economy and, therefore, proposes a rereading of "classical economics", adding that it would have been an ethical impoverishment due to its overly linked to mathematical reason structure and focus on individual interest. Seeking a solution that would avoid utilitarianism, Sen developed the theory of capabilities, which proposes to consider the interpersonal comparisons of "utility." Thus, we intend to address the issue of the fact-value dichotomy, based on the thought of Putnam and Sen, pointing out the possible consequences that the arguments raised generate for philosophical perception of political science, and notions of reason applicable to normative issues.